A new approach to model sensitivity of graphene-based gas sensors. (20th March 2015) - Ghadiry, Mahdiar; Ismail, Razali; Naraghi, Bahareh; Taheri Abed, Sanaz; Kavosi, Daruosh; Fotovatikhah, Farnaz
Abstract: Carbon-based sensors are attractive because of their excellent sensing capability. In this paper, we propose a new approach to analytically model the sensitivity of these devices based on graphene. The model relies on the surface potential and current of the device. For the first time, we included ionization in the modelling and examined the importance of this effect. In order to validate the model, the results are compared with experimental data from a fabricated device.